2012
DOI: 10.1074/jbc.m111.318733
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Suppresses T Cell Activation by Blocking Ca2+ Mobilization and Nuclear Factor of Activated T Cells (NFAT) Activation

Abstract: Background: Curcumin can overcome CsA resistance. However, the molecular mechanism is unknown. Results: Curcumin blocks T cell stimulation-induced Ca 2ϩ mobilization and thereby prevents NFAT activation, a mechanism different from CsA. Conclusion: Curcumin is an immunosuppressive phytochemical that blocks Ca 2ϩ signaling. Significance: The study demonstrates for the first time that curcumin is a potent inhibitor of NFAT activation via blocking Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 42 publications
(55 reference statements)
2
22
0
Order By: Relevance
“…This may reflect a suppressive effect of curcumin and piperine on T cell-mediated functions as reported in several previous studies [40-44]. For example, it has been shown that dietary curcumin in mice suppresses CD4 + T cell proliferation and IL-2 production [43] while in vitro curcumin supplementation inhibits T cell activation [44], human peripheral blood mononuclear cell proliferation and IL-2 production [40,42], and IL-2 synthesis as well as IL-2 signaling in mouse CD4+ T cells [41]. Although little information is available for piperine in this regard, some studies have indeed suggested that piperine may inhibit T cell-related functions [19,45].…”
Section: Discussionsupporting
confidence: 65%
“…This may reflect a suppressive effect of curcumin and piperine on T cell-mediated functions as reported in several previous studies [40-44]. For example, it has been shown that dietary curcumin in mice suppresses CD4 + T cell proliferation and IL-2 production [43] while in vitro curcumin supplementation inhibits T cell activation [44], human peripheral blood mononuclear cell proliferation and IL-2 production [40,42], and IL-2 synthesis as well as IL-2 signaling in mouse CD4+ T cells [41]. Although little information is available for piperine in this regard, some studies have indeed suggested that piperine may inhibit T cell-related functions [19,45].…”
Section: Discussionsupporting
confidence: 65%
“…It is also noteworthy that the mode of sustained Ca 2+ cyt rise in CUR+CA-treated AML cells is distinct from those proposed for polyphenols. Specifically, elevation of Ca 2+ cyt did not involve the previously reported modulation of store-operated [45] or voltage-dependent [46] Ca 2+ entry because the removal of extracellular Ca 2+ did not affect the extent of CUR+CA-induced apoptosis (Figure 3A). Likewise, accumulation of Ca 2+ cyt did not result solely from massive Ca 2+ ER release despite the fact that CUR is a known inhibitor of SERCA [43].…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies have found that curcumin may inhibit cytokine expression and reduce inflammation, as well as inhibit the secretion of TGF-β (34). These studies suggested that curcumin may be beneficial during fibrosis, and as multiple pathways, including inflammation, TGF-β and KL have been demonstrated to be involved in kidney fibrosis the current study investigated whether curcumin alleviates fibrosis through a KL-mediated pathway, while it is possible that other pathways are involved.…”
Section: Discussionmentioning
confidence: 95%